The Moderating Role of Corporate Governance in the Relationship Between Transfer Pricing and Tax Avoidance - Dharmawan, Nyoman Ari Surya; Saputra, Komang Adi Kurniawan; Wigarba, I Gede Arya (Jurnal Ilmiah Akuntansi dan Bisnis, 2025)
This study investigates the relationship between transfer pricing (TP) and tax avoidance (TA), with corporate governance (CG) serving as a moderating variable. The research focuses on manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. The sample comprises 180 observations derived from 30 multinational manufacturing companies, selected through a purposive sampling technique based on specific criteria. Panel data regression analysis was employed, utilizing models both with and without the moderating variable. The findings indicate that TP positively influences TA, suggesting that transfer pricing practices are associated with higher levels of tax avoidance. However, the study also reveals that strong CG can mitigate the positive impact of TP on TA, thereby underscoring the moderating role of effective governance mechanisms. These results highlight the importance of robust CG in reducing tax avoidance practices facilitated through transfer pricing. This study offers practical recommendations for strengthening corporate governance and implementing stricter regulatory oversight of transfer pricing activities. By enhancing governance frameworks, policymakers and companies can better address the ethical and financial implications of tax avoidance in multinational enterprises. Keywords : transfer pricing, tax avoidance, corporate governance, multinational manufacturing compani